Do shared self-expanding activities have to be physically arousing?. (September 2019) - Tomlinson, Jennifer M.; Hughes, Erin K.; Lewandowski, Gary W.; Aron, Arthur; Geyer, Rachel
Participation in shared self-expanding activities benefits both relationships and the self. However, most studies use tasks that combine self-expansion and arousal within one activity, making it difficult to know what drives the benefits. We tested the distinct effects of self-expansion and arousal in four studies. In Studies 1 and 2, 35 married couples and 106 friend pairs completed experiments manipulating self-expansion and arousal. Self-expansion (and not arousal) predicted relationship and individual outcomes. In Studies 3 and 4, 200 married individuals and 202 individuals thinking of a close friend reported perceptions of self-expansion and arousal during activities. Simultaneous regressions showed self-expansion, controlling (or not controlling) for arousal, predicted relationship, and individual outcomes. Results suggest that self-expansion is central for deriving benefits of shared activities, while arousal does not seem to be necessary.